Sighpost Assistant Prototype Design: A Wayfinding Application to Assist The Independence of The Visually Impaired in Mobility Through Understanding The Concept of Space - Wulandari, Putri Lagenda; Nurjanah, Iza; Sasmita, Desri; Sakinah, Diffany Noriko; Nurhastuti, Nurhastuti; Marlina, Marlina; Martias , Martias (Angstrom Centre of Education, 2024)
This research presents a study related to the creation and design of direction applications to help blind independence in mobility through understanding the concept of space. This research aims to help blind independence in carrying out daily activities by understanding the concept of space in their environment. This research uses a development method, namely the prototype development model. However, this research is limited only to the development of the Signpost Assistant application design. It is hoped that this research will be continued and will produce a finished product. Based on the results of data collection and prototype development carried out, it can be concluded that Signpost Assistant is an application that is quite easy to use and is needed by blind people.